Zostera marina L.: Supercritical CO2-extraction and mass spectrometric characterization of chemical constituents recovered from seagrass - Razgonova, Mayya P.; Tekutyeva, Lyudmila A.; Podvolotskaya, Anna B.; Stepochkina, Varvara D.; Zakharenko, Alexander M.; Golokhvast, Kirill S. (Separations)
Three types of Zostera marina L. collection were extracted using the supercritical CO2-extraction method. For the purposes of supercritical CO2-extraction, old seagrass ejection on the surf edge, fresh seagrass ejection on the surf edge and seagrass collected in water were used. Several experimental conditions were investigated in the pressure range 50-350 bar, with the used volume of co-solvent ethanol in the amount of 1% in the liquid phase at a temperature in the range of 31-70 degrees C. The most effective extraction conditions are: pressure 250 Bar and temperature 60 degrees C for Z. marina collected in sea water. Z. marina contain various phenolic compounds and sulfated polyphenols with valuable biological activity. Tandem mass-spectrometry (HPLC-ESI-ion trap) was applied to detect target analytes. 77 different biologically active components have been identified in Z. marina supercritical CO2-extracts. 38 polyphenols were identified for the first time in Z. marina.